Common sequence variant in lipoprotein lipase gene conferring triglyceride response to fibrate treatment. (February 2009) - Chien, Kuo-Liong; Lin, Yen-Lin; Wen, Hui-Chin; Lin, Hsing-Pei; Yen, Ching-Tzu; Lin, Shu-Wha; Kao, Jau-Tsuen
Aims: Little is known about whether the variations in the lipoprotein lipase ( LPL ) and apolipoprotein gene cluster ( APOA1/C3/A5 ) confer appreciable triglyceride lowering after fibrate treatment among patients with hypertriglyceridemia.Materials & methods: We investigated whether variations in these genes confer a triglyceride lowering response after fibrate treatment among 145 patients with hypertriglyceridemia receiving 6 months of fibrate treatment.Results: Overall triglycerides decreased from 746.2 mg/dl to 465.9 mg/dl and the mean percentage of triglyceride lowering was 50.7 ±± 38.6%. A total of two polymorphisms, LPL IVS8 +483T>G and APOA1 +2169G>C, were associated with a significant percentage of triglyceride lowering. Common haplotype effects of LPL on the triglyceride lowering percentage were significant (p = 0.002) and the percentage of variance explained by the LPL haplotype was 7.5%. One common LPL haplotype encompassing three polymorphisms was associated with a -45.40% change (p < 0.001) and risk of a 5.9-fold risk for developing a poor response (95% confidence interval: 1.11––31, p = 0.037), compared with the most frequent LPL haplotype.Conclusion: Our results indicate that the LPL gene variant may cause triglyceride lowering after fibrate treatment among patients with hypertriglyceridemia.